(untitled) (Community Based Medical Journal, 2026)
Incidence of acute coronary syndrome (ACS) is increasing day by day. ECG is the first line method to diagnose ACS. ST-segment elevation or depression determines the presence or absence of IHD or STEMI / NSTEMI. Augmented limbs leads are used, aVR, aVF and aVL to obtain information from heart. Often lead aVR is ignored; ST-segment elevation in aVR may determine left main coronary artery stenosis (LMCAS). A cross-sectional study was conducted in the Department of Cardiology, Punjab Institute of Cardiology, Lahore, Pakistan, from June 2015 to July 2016, to determine the correlation between ST-segment elevation in lead aVR and severity of LMCA stenosis on angiography in ACS patients. A total of 60 patients with acute coronary syndrome with ST-segment elevation in lead aVR undergoing angiography were included through non-probability, purposive sampling. The mean age was 56.13±9.56 years. There were 53(88.33%) males and 7(11.67%) females; male-female ratio was 7.57:1. There were 27(45%) patients with diabetes mellitus, 39 (65%) patients had hypertension, 5(8.3%) patients had hyperlipidemia and 25 (41.67%) were smokers. There were 31(51.7%) patients who had V1 1mm and 29(48.3%) had V1 2mm. The mean value of aVRST was 1.08±0.54 mm. LMCAS was found in 25(41.7%) cases, while 14 cases had 0.5mm aVRST, there was only one case who had LMCAS. out of 43 cases who had 1-2mm aVRST, 21 had LMCAS and among 3 cases of aVRST 2-3mm, all had significant LMCAS detected on angiography (p<0.05). There was positive relationship between aVRST and LMS (r=0.459, p=0.000). To conclude, a weak but positive relationship present between LMCAS and ST-segment elevation in lead aVR, which may help predict the severity of LMCAS on the basis of ECG instead of going directly for angiography. CBMJ 2026 January: vol. 15 no. 01 P:134-137